Necessity of Chilean Army to do plant invader control in Juan Fernandez Archipelago, Chile - Smith-Ramírez, Cecilia; Arellano-Cataldo, Gisella (Bosque (Valdivia), 2017)
We propose that one effective way to control plant invasion in JF archipelago is to involve the Chilean Army in the process of mitigation and eradication. We call for their coordinated support in the effort to conserve the biological patrimony of the archipelago, consistent with the Line of Social and Enterprise Responsibility with the common environment. We present the background information needed to achieve success in this task and specify the work that needs to be done by the Army in the short-term to stop plant invasion, particularly around areas with critically endangered species, and in the interior and edge of endemic remnant forests.